Meningkatkan Hasil Belajar dan Motivasi Belajar Matematika Selama Pandemi Covid-19 melalui Penggunaan Aplikasi Google Classroom pada Siswa Kelas VIII-3 SMP Negeri 1 Sei Bingai Tahun Pelajaran 2022-2021 - Lamsah Saragih (Keguruan, 2022)
This study aimed to improve the learning outcomes on Mathematics subjects and learning motivation in class VIII-3 of SMP Negeri 1 Sei Bingai in 2020-2021 academic year through the using of Google Classroom application during the Covid-19 Pandemic for